'Battleship Femininity' deconstructed: Unmasking the myth of Eva Dahlbeck and Ingmar Bergman. Issue 2 (1st June 2021) - Kobayashi, Saki
The Swedish film star Eva Dahlbeck (1920‐2008) is now remembered mainly for her contributions to Ingmar Bergman's comedies in the 1950s. The epithet 'Pansarskeppet kvinnligheten' ('Battleship Femininity'), allegedly given to her by the director, has integrated her stardom into the myth-making process driven by Bergman and the press. This can erroneously give him sole credit for Dahlbeck's fame despite her already established star status. To reconsider such an auteurist misconception, this article examines Dahlbeck's stardom from 1946 to 1956, drawing on Richard Dyer's seminal theorization of a film star as a media construction. By analysing Dahlbeck's star image and its relationship to three characters she plays in Bergman's films, the article situates these films in the dynamics formed by diverse media texts and elucidates their historical and cultural context while also providing a case study of film stardom in post-war Sweden.